FAKTOR-FAKTOR YANG MEMPENGARUHI RESPON AREAL KEDELAI DI PROVINSI JAMBI - Gustiana, Gustiana; Alamsyah, Zulkifli; Sri Nurchaini, Dewi (Universitas Jambi, 2018)
The harvest area of soybeans tends to fluctuate since 2000-2015. The decrease in soybean harvest area caused by competitiveness or soybean price that less profitable than other food commodities. It is caused by declining interest of farmers to plant soybeans, it can be seen from the decline in the number of harvest area that steadily decreasing from year to year (BPS Province of Jambi, 2015). This research aims to determine the factors that influence the soybean area response in the Province of Jambi and elasticity in the short term and long term. The data used in this research is secondary data time series for 16 years (2000-2015). The problems in this research were analyzed by quantitative descriptive method using multiple linear regression analysis model. Elasticity calculated in the long term and short term. Based on the results of this research has known factors that influence the harvest area, that is the price of soybean in the previous year, the price of rice in the previous year, the price of corn in the previous year and harvested area in the previous year. In the short term and long term the soybean acreage is quite responsive to price changes, although in the short term not more responsive than the long term. It shows that the effect of price changes more responded by farmers to expand the acreage (extensification) than by increasing productivity (intensification).